(untitled) (CAHIERS MAGELLANES-NS, 2024)
The study aimed to validate the probiotic properties of non-lactose fermentative bacteria through a range of experimental assessments which include acid and bile tolerance, cell adhesion, hydrophobicity and hepatoprotective nature. It also focuses to evaluate their efficacy using animal model based drug delivery system and post drug delivery analysis of vitals. Probiotics are commonly defined by their ability to confer health benefits through their interaction with the host's microbiota, often demonstrated by their ability to ferment lactose. However, this study focused on non-lactose fermentative strains, exploring their potential as probiotics. Laboratory tests included assays for adherence to intestinal epithelial cells, resistance to gastric acidity and bile salts. The efficacy was assessed using Sprague-Dawley animal model, where various doses of the bacterial strains were administered to laboratory animals, and subsequent health parameters were monitored. Results indicated that while the bacteria did not ferment lactose, they exhibited other probiotic characteristics such as high resistance to harsh gastrointestinal conditions and beneficial effects on gut health in animal models. These findings support the potential of non-lactose fermentative bacteria as probiotics, expanding the scope of probiotic candidates beyond traditional lactose-fermenting strains. Further studies are warranted to elucidate the mechanisms behind their beneficial effects and to evaluate their potential in human applications. All the 3 isolates Lactobacillus plantarum (IS), Lactobacillus fermentum(IL) and Bacillus mojavensis (DF) which were isolated and identified in our previous work are further processed in this study.